Political Accountability and Real Authority of Government Bureaucracy - Marina Dodlova (Center for Economic Studies and ifo Institute (CESifo), 2013)
In a country with weak institutional constraints on the executive, the real power might belong to the government bureaucracy rather than to an autocratic leader. We combine the Aghion-Tirole definition of formal and real authority with the Barro-Ferejohn model of political agency to study the relationship between the accountability of elected politicians and the extent to which their subordinate bureaucrats have real decision-making power. We show that the lower is the level of political accountability, the lower should be real authority at the bottom of the government hierarchy. Empirically, we find that in countries with lower political accountability those in political power have less authority over the public administration. On the contrary, countries with higher political accountability have bigger governments in terms of administration employment.
Keywords: D72; D73; D83; H11; 330; political accountability; bureaucracy; real authority; decision-making; government employment